Analisis Keaktifan Belajar Siswa Menggunakan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Kahoot! pada Pembelajaran Matematika sI SMAM 7 Surabaya - Maulina, Veny (J-SES : Journal of Science, Education and Studies, 2024)
: This study aims to analyze the use of Kahoot! in the Problem Based Learning (PBL) learning model on student learning activity in class XI-2 SMAM 7 Surabaya. This study uses a qualitative descriptive method with data collection techniques through observation and interviews. The research subjects consisted of 22 students who participated in learning using Kahoot!. The results of the study show that the use of Kahoot! can increase student learning activity, with the aspect of writing and emotional activities obtaining the highest percentage of 91%, followed by visual and mental aspects 89%, listening activities 86%, and oral activities 80%. These findings show that Kahoot! Not only does it help students understand the material in a more fun way, but it also encourages them to participate more actively in learning. Keywords: Active Learning, Kahoot!, Problem Based Learning (PBL)